Residential radon, EGFR mutations and ALK alterations in never-smoking lung cancer cases. Issue 5 (6th October 2016) - Ruano-Ravina, Alberto; Torres-Durán, María; Kelsey, Karl T.; Parente-Lamelas, Isaura; Leiro-Fernández, Virginia; Abdulkader, Ihab; Abal-Arca, José; Montero-Martínez, Carmen; Vidal-García, Iria; Amenedo, Margarita; Castro-Añón, Olalla; Golpe-Gómez, Antonio; et al.
The aim of this study was to assess if residential radon exposure might cause EGFR mutations or ALK rearrangements in never-smokers. We designed a multicentre case–control study in a radon-prone area (Galicia, Spain); only lung cancer cases were included in the study. We obtained residential radon measurements and clinical information for all the participants. We compared the median values of residential radon between patients with EGFR mutations or ALK rearrangements versus those without them. 323 patients were included. Median age was 70 years and 19.5% were males. 42 and 15% of patients were EGFR - and ALK -positive, respectively. The most frequent EGFR alterations were exon 19 deletions and exon 21 (L858R) single-point substitution mutations. ALK -positive patients were 10 years younger than ALK -negative patients. Residential radon levels were two-fold higher in patients with exon 19 deletions compared with patients with exon 21 (L858R) single-point substitution mutations (216 versus 118 Bq·m −3 ; p=0.057). There were no differences in residential radon levels by EGFR mutation status. ALK -positive patients (n=12) essentially had two-fold residential radon levels compared with ALK -negative patients (290 versus 164 Bq·m −3, respectively). Residential radon may have a role in the molecular signature of lung cancer in never-smokers, although more studies with larger sample sizes are needed to support this hypothesis. Residential radon might cause genetic alterations in driver genes for lung cancer in never-smokers http://ow.ly/1u4P302JdBs